Effect of food allowance on diet selectivity and intake of pearl millet (Pennisetum glaucum) stover leaves by sheep - Fernández Rivera, S.; Midou, A.; Marichatou, H. (1994)
The influence of food allowance or level of food excess on diet selectivity and intake by sheep given pearl millet stover leaves, and the potential feeding value of the food leftovers (L) were studied. Animals were given food at four levels of L (100, 300, 500 and 700 g dry matter (DM) per day). All sheep received different food allowances (A, g DM per day) and had different L/A and A/M (g dm per kg M) ratius. An additional treatment consisted of feeding the leftovers from the two highest levels of food excess to six rams to have 300 g DM of L per day. A diet supplement was given to provide sufficient rumen degradable protein and sulphur to sustain microbial activity. Variances of organic matter (DM) digestibility (OMD) and intake of both DM and digestibile OM (DOMI) of the original millet leaves were analysed. Results suggest that DOMI of millet stover should be determined at L/A much higher than the traditionally recommended, and support the hypothesis that farmers could benefit from feeding millet stover at high allowances to animals of high economic value and give the leftovers to less valuable or less selective stock.